The Effectiveness of Group Counseling Services A Client-Centered Approach to Increase the Confidence of Students Who are Victims of Body Shaming - Pulungan, Wafiq Syafinaturohmah; Harahap, Ade Chita Putri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This quantitative research with an experimental approach aims to determine the effectiveness of group counseling using a client-centered approach to increase the self-confidence of students who are victims of body shaming at MTs 2 Medan. The study population consisted of 150 students, and the sample was taken using purposive sampling. Data was collected by performing pre-tests and post-tests before and after the group counseling sessions using the client-centered approach. The data were analyzed using the Wilcoxon Signed Rank Test with SPSS. The results showed that after the group counseling sessions, there was an increase in self-confidence among the students: 5 students experienced an increase in self-confidence to the high category, and three other students experienced an increase to the very high category. The data analysis using the Wilcoxon Signed Rank Test revealed that the sig (2-tailed) value was less than 0.05, specifically 0.011, indicating that group counseling using the client-centered technique effectively enhances the self-confidence of students who experience body shaming.